2005
DOI: 10.1161/01.str.0000190006.88896.d3
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stromal Cells That Enhanced Fibroblast Growth Factor-2 Secretion by Herpes Simplex Virus Vector Improve Neurological Outcome After Transient Focal Cerebral Ischemia in Rats

Abstract: Background and Purpose-Fibroblast growth factor-2 (FGF-2) administration and bone marrow stromal cell (MSC) transplantation could improve neurological deficits after occlusive cerebrovascular disease. In the present study, we examined the effects of neurological improvement after transient middle cerebral artery occlusion (MCAO) in rats by a novel therapeutic strategy with FGF-2 gene-transferred MSCs by the herpes simplex virus type 1 (HSV-1) vector. Methods-Adult Wistar rats were anesthetized. Nonmodified M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 23 publications
4
53
0
4
Order By: Relevance
“…Furthermore, MSCs have shown efficiency as therapeutic vectors. Indeed, these cells, genetically modified to overexpress, for example, brain-derived neurotrophic factor (Kurozumi et al, 2004;Nomura et al, 2005), glial cell line-derived neurotrophic factor (Kurozumi et al, 2005), and fibroblast growth factor (Ikeda et al, 2005), were therapeutically more efficient than nonmodified MSC. Recently, a study reported beneficial effects of combined treatments, that is bone marrow cells and adenovirus overexpressing metalloproteinase inhibitors (Baker et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MSCs have shown efficiency as therapeutic vectors. Indeed, these cells, genetically modified to overexpress, for example, brain-derived neurotrophic factor (Kurozumi et al, 2004;Nomura et al, 2005), glial cell line-derived neurotrophic factor (Kurozumi et al, 2005), and fibroblast growth factor (Ikeda et al, 2005), were therapeutically more efficient than nonmodified MSC. Recently, a study reported beneficial effects of combined treatments, that is bone marrow cells and adenovirus overexpressing metalloproteinase inhibitors (Baker et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…59 The potential benefits of FGF2 are supported by studies showing that gene-transfected MSCs expressing this growth factor demonstrated improved functional recovery after stroke compared with MSC transplantation alone. 60 Ex vivo gene transfer has also been attempted with hepatocyte growth factor (HGF) which resulted in decreased apoptosis, increased neuron survival in the ischemic boundary zone and functional improvement. 61 …”
Section: Nonhuman Mscsmentioning
confidence: 99%
“…Many studies on stroke using BMSCs as treatment suggest genetic modification of BMSCs to improve therapeutic potential. Indeed, overexpression of trophic factors such as brain-derived neurotrophic factor (BDNF), fibroblast growth factor-2, and hematopoietic growth factor in gene-modified BMSCs has been demonstrated to improve neurologic outcome in animal models of ischemic stroke [7][8][9] Hypoxia-inducible factor-1 (HIF-1) is an oxygen-sensitive transcription factor [10]. HIF-1 is a heterodimeric protein that consists of a functional HIF-1a subunit and a constitutively expressed HIF-1b subunit.…”
Section: Introductionmentioning
confidence: 99%